Využití Narrow Band Imaging v dia-gnostice časných karcinomů hrtanu - Staníková, L; Kučová, H; Walderová, R; Zeleník, K; Šatanková, J; Komínek, P (Klinicka onkologie, 2015)
BACKGROUND: Narrow band imaging (NBI) is an endoscopic method using filtered wavelengths in detection of microvascular abnormalities associated with preneoplastic and neoplastic changes of the mucosa. The aim of the study is to evaluate the value of NBI endoscopy in the dia-gnosis of laryngeal precancerous and early stages of cancerous lesions and to investigate impact of NBI method in prehistological diagnostics in vivo. MATERIALS AND METHODS: One hundred patients were enrolled in the study and their larynx was investigated using white light HD endoscopy and narrow band imaging between 6/ 2013- 10/ 2014. Indication criteria included chronic laryngitis, hoarseness for more than three weeks or macroscopic laryngeal lesion. Features of mucosal lesions were evaluated by white light endoscopy and afterwards were compared with intra-epithelial papillary capillary loop changes, viewed using NBI endoscopy. Suspicious lesions (leukoplakia, exophytic tumors, recurrent respiratory papillomatosis and/ or malignant type of vascular network by NBI endoscopy) were evaluated by histological analysis, results were compared with prehistological NBI dia-gnosis. RESULTS: Using NBI endoscopy, larger demarcation of pathological mucosal features than in white light visualization were recorded in 32/ 100 (32.0%) lesions, in 4/ 100 (4.0%) cases even new lesions were detected only by NBI endoscopy. 63/ 100 (63.0%) suspected lesions were evaluated histologically - malign changes (carcinoma in situ or invasive carcinoma) were observed in 25/ 63 (39.7%). Prehistological diagnostics of malignant lesions using NBI endoscopy were in agreement with results of histological examination in 23/ 25 (92.0%) cases. The sensitivity of NBI in detecting malignant lesions was 89.3%, specificity of this method was 94.9%. CONCLUSION: NBI endoscopy is a promising optical technique enabling in vivo differentiation of superficial neoplastic lesions. These results suggest endoscopic NBI may be useful in the early detection of laryngeal cancer and precancerous lesions.
Keywords: sliznice hrtanu; nádory hrtanu; laryngoskopie; Laryngeal Neoplasms; Laryngoscopy; Laryngeal Mucosa; Narrow Band Imaging; lidé; spinocelulární karcinom; úzkopásmové zobrazení; Early Detection of Cancer; Humans; časná detekce nádoru; Carcinoma, Squamous Cell